(untitled) (Indian Journal of Animal Production and Management, 2017)
An investigation was carried out to study the socio – economic profile and constraints faced by thebuffalo milk producers in Guntur district of Andhra Pradesh. It was observed that majority of milk producers belonged to middle age (31- 55 years) group followed by old (above 55 years) and young age (upto 30 years) groups in small farmers, commercial and landless milk producers. Most of the commercial milk producers and small farmers belonged to open category (kamma / kapu / reddy caste )followed by backward caste and scheduled caste. Majority of buffalo milk producers were literate ranging from primary to graduation level of education. Majority of milk producers in small farmer category had agriculture as main occupation and dairying as subsidiary occupation. Landless milk producers had agriculture labour as main occupation and dairying as subsidiary occupation, whereas, commercial milk producers had dairying as main occupation. Majority of commercial milk producers had more extension contact and mass media exposure as compared to small farmers and landless milk producers.High cost of pure bred buffaloes, feed ingredients, non remunerative price for milk, feed and fodder shortage and high incidence of repeat breeding in buffaloes were found to be major constraints felt by the milk producers in the study area. Problem of silent heat, repeat breeding, lack of sufficient knowledge to the farmers about scientific feeding and management and inadequate facilities for diagnostic purpose were observed to be constraints felt by the field veterinarians in Guntur district.